THE IMPORTANCE OF STUDENT‘S INDEPENDENT FRONTAL EXPERIMENTS IN PHYSICS - O’rozov Abdukholiq Nurmamatovich (Bright Mind Publishing, 2025)
This article analyzes the problems of developing students' observation and thinking skills in teaching physics, as well as arousing interest in the problems of the world around them and their solutions. Physics during the lesson and the use of virtual laboratory programs in laboratory work plays a key role in improving students' information and communication skills. Modern information technologies accelerate all stages of educational processes. In this regard, based on the use of information technologies, we can observe an increase in the quality and efficiency of the educational process, as well as the activation of students' cognitive activity.
Keywords: Physics, modern information technologies, physical events, electricity and magnetism teaching, laboratory work, physics tools, experiment.